Effect of analgesics and their derivatives on antibiotic resistance of environmental microbes - Dhanapal, L P (Water science and technology : a journal of the International Association on Water Pollution Research, 2009)
This research is a preliminary study conducted to determine the effects of aspirin (acetyl-salicylic acid) and salicylic acid (analgesics and their derivatives) on the antibiotic resistance of ammonia oxidizing bacterium (AOB) (a non-pathogenic environmental microbe) cultured from the Texas Tech University-Water Recovery System that treats a space related wastewater for NASA. The effect of salicylic acid was investigated by obtaining the minimal inhibition concentration (MIC) of antibiotics (amoxicillin, ciprofloxacin, and nalidixic acid) in the presence of aspirin and salicylic acid. The possibility of transfer of resistance genes between unrelated species was investigated by analyzing the similarity of the AcrA protein (a multi-drug efflux protein) in Nitrosomonas europaea, Escherichia coli and Salmonella enterica. The protein alignment analysis was done using ExPASy, a proteomics tool. The results of this preliminary study indicated that the antibiotic resistance of AOBs increased in the presence of aspirin and salicylic acid and similarities in the AcrA protein of different species indicated the likelihood of possible resistance transfer between the species. This paper high lights the importance of research and further investigation on antibiotic resistance and resistance transfer, highlighting the number of parameters that should be considered while assessing antibiotic resistance in environmental samples